A systems approach to the exploration of research activity and relationships within a local authority - Judith F. Fynn; John Jones; Andy Jones (BMC, 2021)
Abstract Background Organizations with responsibilities for public health are increasingly required to use evidence-based practice to inform programme delivery, requiring research to generate relevant evidence, and dissemination and use of evidence to inform decisions and practices. Understanding how relationships between organizational structures, systems and processes influence evidence-based practices is critical to improving practice at both an institutional and system level, yet how these relationships should best operate is not well understood. Understanding how to better support research within local authorities, the elected administrative bodies responsible for services including public health at a regional level in the United Kingdom, is a priority for the National Institute for Health Research (NIHR) Public Health Research. This study is based on Norfolk County Council, a local authority in the east of England. We aimed to apply a systems perspective to develop a better understanding of the structures, systems and processes that support a local authority in becoming research-active, identifying gaps in understanding and recommendations for action to address them. Methods Taking a participatory action research approach, we applied qualitative methods to explore research activity and relationships in Norfolk County Council. We surveyed employees and used network analysis to map individuals, departments and external partners involved in research activities and the connections between them. We then applied participatory approaches to conduct a series of focus groups and semi-structured interviews to explore stakeholders' experiences and perceptions of being involved in research at, or with, the authority, and their ideas for recommendations for future actions. Results A range of research activity is undertaken at the local authority, with an emphasis on applied work to improve service delivery. We identified several examples of effective practice and models of research collaboration in some departments. Challenges such as limitations in resources, capacity and knowledge exchange were evident, yet there was a readiness amongst key stakeholders to develop and implement actions that may better support the authority in becoming more research-active. Conclusion In large complex organizations, a key challenge is how to share learning across teams and implement good practice at an organizational and system level. Our findings highlight the potential for developing improved collaborative partnership models and systems to support sustainable processes and practices for research and knowledge exchange at an institutional and interorganizational level. The insights gained and shared will support other local authorities and similar large, multilevel organizations with responsibilities for evidence-based public health to explore their own setting and implement change where needed, and provide stimulus for further research into system-level change.